2017
DOI: 10.5194/acp-17-15121-2017
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of traffic exhaust contributions to ambient carbonaceous submicron particulate matter in an urban roadside environment in Hong Kong

Abstract: Abstract. Road traffic has significant impacts on air quality particularly in densely urbanized and populated areas where vehicle emissions are a major local source of ambient particulate matter. Engine type (i.e., fuel use) significantly impacts the chemical characteristics of tailpipe emission, and thus the distribution of engine types in traffic impacts measured ambient concentrations. This study provides an estimation of the contribution of vehicles powered by different fuels (gasoline, diesel, LPG) to car… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 79 publications
(100 reference statements)
1
14
0
Order By: Relevance
“…Another plausible reason for the elevated OC observed in wintertime is the enhanced partitioning of semivolatile organic compounds (SVOCs) into the particle phase due to lower temperature and higher organic aerosol loading. Previous studies at the same monitoring site show that VE-related organic aerosol (derived from PMF analysis of organic aerosol mass spectra) decreases by 40 % in summer relative to spring despite consistency in traffic flow volume, which points to a sizable influence of the gas-particle partitioning of SVOCs (Lee et al, 2017).…”
Section: Oc Trendsmentioning
confidence: 90%
See 4 more Smart Citations
“…Another plausible reason for the elevated OC observed in wintertime is the enhanced partitioning of semivolatile organic compounds (SVOCs) into the particle phase due to lower temperature and higher organic aerosol loading. Previous studies at the same monitoring site show that VE-related organic aerosol (derived from PMF analysis of organic aerosol mass spectra) decreases by 40 % in summer relative to spring despite consistency in traffic flow volume, which points to a sizable influence of the gas-particle partitioning of SVOCs (Lee et al, 2017).…”
Section: Oc Trendsmentioning
confidence: 90%
“…The success has been verified by results from an ad hoc roadside study and a study comparing the emissions in a local tunnel between 2003 and 2015 (Lee et al, 2017;Wang et al, 2018). Most HK studies in the past only reported overall PM vehicle contributions due to the lack of separate local source profiles for diesel and gasoline vehicles and constraints in the PMF model posed by a lack of vehicle type specific tracers (Li et al, 2012;Huang et al, 2014;Cheng et al, 2015;Sun et al, 2016). Some studies achieved the separation either by using nonlocal source profiles in the CMB model or by coupling vehicle-type-specific traffic data collected in a short period with aerosol-mass-spectrometry-based PMF (Zheng et al, 2006;Lee et al, 2017).…”
Section: Introductionmentioning
confidence: 87%
See 3 more Smart Citations